Talking about Ideal Civil-Military Relationship: Comparation Cases between Military in Indonesia and India in Dealing with Covid-19 Pandemic - Taju, Atalia Eureka Putri; Saadah, Kholifatus (Department of International Relations Universitas Pertamina, 2021)
The relationship between civil and military has many dimensions, and this relationship may be ideal. This article uses Huntington and Feaver's preferences to explain the ideal civil-military relationship in India and Indonesia through case studies of handling the COVID-19 pandemic. The choice of the two countries was due to Indonesia and India showing the dynamics of the relationship between civilians and the military from being quite harsh to be ideal. The ideal civil-military relationship can be described as a military subject to civilian control. However, this does not mean that the civilian government has total power over the military; Instead, the control in question illustrates that the military is a professional institution and is ready to protect its citizens. Civilians no longer see the military as being in the position of who will guard the guardian, but how to control your guardian so that there is no escalation of conflict or coups between the military and civilians. Through these ideal civil and military relations, the military-assisted handling of the pandemic has yielded satisfactory results for both countries.